Executive compensation, firm performance, and corporate governance in China: evidence from firms listed in the Shanghai and Shenzhen stock exchanges - Takao Kato; Cheryl Long (Institute for the Study of Labor (IZA), 2005)
This paper provides evidence on how executive compensation relates to firm performance in listed firms in China. Using comprehensive financial and accounting data on China's listed firms from 1998 to 2002, augmented by unique data on executive compensation and ownership structure, we find for the first time statistically significant sensitivities and elasticities of annual cash compensation (salary and bonus) for top executives with respect to shareholder value in China. In addition, sales growth is shown to be significantly linked to executive compensation and that Chinese executives are penalized for making negative profit although they are neither penalized for declining profit nor rewarded for rising profit insofar as it is positive. Perhaps more importantly, we find that ownership structure of China's listed firms has important effects on pay-performance link in these firms. Specifically state ownership of China's listed firms is weakening pay-performance link for top managers and thus possibly making China's listed firms less effective in solving the agency problem. As such, ownership restructuring may be needed for China to successfully transform its SOEs to efficient modernized corporations and reform its overall economy.
Keywords: M52; M12; J33; P31; P34; O16; G30; O53; G15; 330; executive compensation; firm performance; corporate governance; ownership structure; China; transition economies